1975
DOI: 10.1111/j.1432-1033.1975.tb02476.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Ketogenesis and Its Control

Abstract: 1. Two mitochondrial forms of acetoacetyl-CoA thiolases designated as enzyme A and enzyme B were crystallized from ox liver. They could be shown to be homogenous by polyacrylamide gel electrophoresis.2. In direction of acetoacetyl-CoA cleavage enzyme A shows a double competitive substrate inhibition when acetoacetyl-CoA is varied at different fixed CoA concentrations. With enzyme B a parallel kinetic pattern is obtained when acetoacetyl-CoA is varied at different fixed CoA concentrations. In direction of aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 35 publications
3
28
0
1
Order By: Relevance
“…For example, the recent report of McKean et al [6] suggests that acetoacetyl-CoA levels may modulate activity of acyl-CoA dehydrogenase. In addition, acetoacetyl-CoA thiolase [7, 101 have been postulated to be rate-limiting in ketogenesis.Evaluation of the role of HoMeGlt-CoA cycle enzymes in regulation of ketogenesis is difficult due to the lack of a detailed Abbrcviutions. HoMeGlt, 3-hydroxy-3-methylglutaryl; Hepes, 4-(2-hydroxyethy1)-I-piperazineethanesulfonic acid.…”
mentioning
confidence: 99%
“…For example, the recent report of McKean et al [6] suggests that acetoacetyl-CoA levels may modulate activity of acyl-CoA dehydrogenase. In addition, acetoacetyl-CoA thiolase [7, 101 have been postulated to be rate-limiting in ketogenesis.Evaluation of the role of HoMeGlt-CoA cycle enzymes in regulation of ketogenesis is difficult due to the lack of a detailed Abbrcviutions. HoMeGlt, 3-hydroxy-3-methylglutaryl; Hepes, 4-(2-hydroxyethy1)-I-piperazineethanesulfonic acid.…”
mentioning
confidence: 99%
“…100 g body wt-") [12]. Obviously only a part of the maximal synthesizing activity can be expressed in vivo due to the inhibitory action of CoASH and acetaacetytCoA on the mAAT [6,7,13]. CoASH may be of physiological importance to the ketogenic rates, for the ketone body production only correlates with the The two forms of the mAAT, A and B, differ in isoelectric points and in specific activities [2].…”
Section: Resultsmentioning
confidence: 99%
“…Huth et al (1975) have pointed out that the activity of the enzyme in the direction of acetoacetyl-CoA synthesis is very much lower than in the thiolytic direction, and from isotopic distribution studies they concluded that the activity of the enzyme may be rate-limiting (Huth et al I 973). One factor which could limit acetyl-CoA acetyltransferase activity in vivo is inhibition by the product of the reaction, acetoacetyl-CoA (Huth et al 1975). Acetoacetyl-CoA also inhibits 3-hydroxy-3-methyl glutaryl (HMG)-CoA synthase (Reed et al r975)-the next enzyme in the ketogenic pathway.…”
Section: Symposium Proceedings I983mentioning
confidence: 99%
“…Since the two forms have different kinetic characteristics (Huth et al 1973) this interconversion may result in a high sensitivity of the activity of the enzyme to changes in the ratio of [acetyl-CoA]: [CoA]. Huth et al (1975) have pointed out that the activity of the enzyme in the direction of acetoacetyl-CoA synthesis is very much lower than in the thiolytic direction, and from isotopic distribution studies they concluded that the activity of the enzyme may be rate-limiting (Huth et al I 973). One factor which could limit acetyl-CoA acetyltransferase activity in vivo is inhibition by the product of the reaction, acetoacetyl-CoA (Huth et al 1975).…”
Section: Symposium Proceedings I983mentioning
confidence: 99%